Beyond speciesism : poems - Ursino, Flavia; Mann, Clare (Terrigal, NSW : USNCOL Pty Ltd, 2020)
This collection of poems by Flavia Ursino - Coleman and friends depicts the existential predicament of animals in contact with exploitive human systems. "Seen" through the eyes of the animals, these evocative poems give a "voice to the voiceless."
Keywords: Australian poetry -- 21st century; Education; Australian